Unilateral Laryngeal Pacing System and Its Functional Evaluation - Taiping Zeng; Zhiping Zhang; Weiwei Peng; Fei Zhang; Baker Y. Shi; Fangyi Chen (Neural Plasticity)
Goal. To establish a reliable instrumental system for synchronized reactivation of a unilaterally paralyzed vocal fold and evaluate its functional feasibility. Methods. Unilateral vocal fold paralysis model was induced by destruction of the left recurrent laryngeal nerve (RLN) in anesthetized dogs. With a micro controller-based electronic system, electromyography (EMG) signals from cricothyroid (CT) muscle on the ipsilateral side were recorded and used to trigger pacing of paralyzed vocalis muscles. The dynamic movement of vocal folds was continuously monitored using an endoscope, and the opening and closing of the glottis were quantified with customized imaging processing software. Results. The recorded video images showed that left side vocal fold was obviously paralyzed after destructing the RLN. Using the pacing system with feedback triggering EMG signals from the ipsilateral CT muscle, the paralyzed vocal fold was successfully reactivated, and its movement was shown to be synchronized with the healthy side. Significance. The developed unilateral laryngeal pacing system triggered by EMG from the ipsilateral side CT muscle could be successfully used in unilateral vocal fold paralysis with the advantage of avoiding disturbance to the healthy side muscles.